PERKEMBANGAN PEMANFAATAN PLTS DI BANDAR UDARA DI DUNIA - Surya Bimantara, Abid; Satya Kumara, I Nyoman; Ariastina, Wayan Gede (Jurnal SPEKTRUM, 2022)
Solar power plants in their application have reached the aviation business. There are already many airports everywhere that use solar power plants as their electrical energy supply. Airports and airfields have a very high opportunity to accommodate solar technology because of open land space. The purpose of this research is to review the advantages or disadvantages of airports solar power plants and conduct a survey of any airports in the world that already have solar power plants. This research used data collected from journals, articles, and news on the internet. Those data include airports that use solar power plants, solar power plants establishment year, airport category, airport location, airport solar power plants capacity, solar power plants type. Hence, the review describes the advantages and disadvantages of PLTS and its specific site everywhere. The results show that 192 airports already use PLTS as an electrical energy supplier. The Asian continent has 43 airports, and there are 5 airports solar power plants in Indonesia. Most of the solar power plant uses an on-grid system